2009
DOI: 10.1242/jcs.058537
|View full text |Cite|
|
Sign up to set email alerts
|

Antioxidant-induced modification of INrf2 cysteine 151 and PKC-δ-mediated phosphorylation of Nrf2 serine 40 are both required for stabilization and nuclear translocation of Nrf2 and increased drug resistance

Abstract: Antioxidants cause dissociation of nuclear factor erythroid 2-related factor 2 (Nrf2) from inhibitor of Nrf2 (INrf2) and so Nrf2:INrf2 can serve as a sensor of oxidative stress. Nrf2 translocates to the nucleus, binds to antioxidant response element (ARE) and activates defensive gene expression, which protects cells. Controversies exist regarding the role of antioxidant-induced modification of INrf2 cysteine 151 or protein kinase C (PKC)-mediated phosphorylation of Nrf2 serine 40 in the release of Nrf2 from IN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 179 publications
(115 citation statements)
references
References 38 publications
4
106
1
4
Order By: Relevance
“…It has been reported that Ser40 within the DLGex motif is phosphorylated by protein kinase C and that this promotes the dissociation of Nrf2 from Keap1 (37)(38)(39)(40). However, in our analysis with an Nrf2 S40E mutant that mimics the phosphorylation of Ser40, Ser40 phosphorylation does not affect the interaction between the DLGex motif and the DC domain of Keap1.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…It has been reported that Ser40 within the DLGex motif is phosphorylated by protein kinase C and that this promotes the dissociation of Nrf2 from Keap1 (37)(38)(39)(40). However, in our analysis with an Nrf2 S40E mutant that mimics the phosphorylation of Ser40, Ser40 phosphorylation does not affect the interaction between the DLGex motif and the DC domain of Keap1.…”
Section: Discussioncontrasting
confidence: 70%
“…It was reported that phosphorylation of Nrf2 Ser40 by protein kinase C promoted the dissociation of Nrf2 from Keap1 and the consequent activation of Nrf2 in response to oxidative stress (37)(38)(39)(40). Because Ser40 was included in Nrf2-DLGex, we were curious about whether the modification of Ser40 has an effect on the association between Nrf2-DLGex and Keap1-DC.…”
Section: Somatic Mutations Encompassing Nrf2-dlg In Human Cancersmentioning
confidence: 99%
“…Another mechanism is that antioxidant-induced protein kinase C (PKC) phosphorylates Nrf2Ser-40, leading to dissociation of Nrf2 from INrf2 and nuclear localization of Nrf2 (5,6). Recently, it has been shown that the two mechanisms work in concert (7). Ultimately, Nrf2 translocates into the nucleus, binds with antioxidant-response elements (ARE) 2 in the promoter regions of cytoprotective genes, and coordinately activates gene expression.…”
mentioning
confidence: 99%
“…PKCδ levels were similar in NL and DS cells (Figure 3d). To evaluate whether Nrf2 phosphorylation in DS cells is dependent on PKCδ kinase activity (Niture et al, 2009), we used the PKCδ inhibitor Gö6983 and also Gö6976, an inhibitor that do not affect PKCδ but interfere PKCα and PKCβ isoforms instead (Gschwendt et al, 1996; Martiny‐Baron et al, 1993; Stempka et al, 1999). Treatment with Gö6983 prevented pNrf2 nuclear translocation in both basal conditions and after PQ treatment, while Gö6976 had no effect (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…Under oxidative conditions, the cysteine‐rich interacting domain in Keap1 changes its conformation, disabling its default association with Nrf2. As a result, Nrf2 accumulates in the cytoplasm and after phosphorylation by PKCδ, pNrf2ser40 translocates into the nucleus where it activates transcription of antioxidant response elements (ARE) (Niture et al, 2009; Villeneuve et al, 2010; Zhang & Hannink, 2003). …”
Section: Introductionmentioning
confidence: 99%